Emergency peripartum hysterectomy at a tertiary care hospital: analysis of epidemiology, clinical profile, indications and outcome - E., Anitha; S., Ramalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Peripartum hysterectomy is a life-saving obstetric procedure that is performed at the time of a caesarean section or postpartum following either vaginal delivery or caesarean section. The purpose of the present study was to determine the incidence, risk factors ,indications ,maternal and neonatal morbidity, mortality and complications of emergency peripartum hysterectomy performed at a tertiary teaching hospital in South India and to compare the results with other reports in literature. Methods: During the period of study between January 2015-December 2016, there were 50 cases of emergency peripartum hysterectomy at Tirunelveli medical college hospital, Tirunelveli, Tamil Nadu, South India. Medical, pathology and operation theatre records were analyzed retrospectively. Details of maternal age, parity, booking status, underlying risk factors, past obstetric history, gestational age at delivery ,mode of delivery ,indications for emergency peripartum hysterectomy, type of operation, intraoperative and post-operative complications, blood components transfusion ,maternal and neonatal outcomes were noted and analyzed. Results: During the 2-year study period there were 50 emergency peripartum hysterectomy out of 14,363 deliveries, a rate of 1 per 294 deliveries (3.4/1000 deliveries). 80% of hysterectomies were performed after caesarean delivery and 20% after vaginal delivery. The two major indications were abnormal placentation (40%) and uterine atony (28%). There were 6 maternal deaths among patients who underwent emergency peripartum hysterectomy during the period of study. Conclusions: Improved antenatal care, correction of anaemia, identification of risk factors for peripartum hysterectomy, timely referral, expedite management, timely decision, availability and liberal use of blood components and appropriate management of post-operative complications by experienced clinical team are the main stay for saving maternal lives. With increasing rate of caesarean section there is rise in the incidence of abnormal placentation.